Nongenomic effects of aldosterone on human renal cells - Köppel, Hannes; Christ, Michael; Yard, Benito A.; Bär, P. C.; Woude, Fokko J. van der; Wehling, Martin (The journal of clinical endocrinology & metabolism, 2003)
The development of chronic renal insufficiency may be partially mediated by the nongenomic action of aldosterone. Here we investigate whether aldosterone could evoke a nongenomic action in primary cultures of human renal cells. Intracellular Ca2+ ([Ca2+]i) and cAMP were measured in human mesangial cells (MC), glomerular visceral epithelial cells (GVEC), and proximal and distal tubular epithelial cells (Ptec and Dtec) in the presence of aldosterone (10-100 nmol/liter) by fura-2 fluorescence and RIA, respectively.In MC, Ptec, and Dtec, aldosterone increased [Ca2+]i within 1 min, whereas in GVEC, only a minor effect was found. Preincubation of cells with spironolactone did not blunt this effect. Hydrocortisone, used at a concentration 100-fold higher than that of aldosterone, did not affect [Ca2+]i. In MC, Ptec, and Dtec, a dose-dependent increase (∼1.3- to 1.5-fold) in intracellular cAMP levels was found.These data demonstrate a nongenomic action of aldosterone in human MC, Ptec, and Dtec. As these effects occur at concentrations close to free plasma aldosterone levels in man, they may be of physiological relevance and may contribute to renal injury.
Gesehen am 25.08.2022